Development of Reverse Phase Ultra-fast Liquid Chromatography Using Ion-pairing Reagent for Quantitative Assessment of Ceftriaxone in Rat Serum and Cerebrospinal Fluid - Padhi, Swarupanjali; Mazumder, Rupa; Bisth, Shradha (Current Pharmaceutical Analysis, 2021)
Background: In case of meningitis, the meninges are inflamed and the blood brain barrier is distorted, therefore, there is no hindrance to drug penetration. The problem arises when the disease is at the verge of cure, the meninges become uninflamed and the permeability of the drug is reduced to such extend that it becomes nearly impossible to maintain the minimum inhibitory concentration of drug at the site of infection. This problem was overcome by formulating ceftriaxone loaded NLCs and administrating it through intraperitoneal route to Wistar Albino rat. For quantitative assessment of drugs in rat serum and cerebrospinal spinal fluid, a new RP-UFLC (reverse-phase ultra-fast liquid chromatography) method has been developed and validated. Objective: Development and validation of RP-UFLC (using ion-pairing reagent) method for accurate estimation of ceftriaxone in rat serum and CSF. Methods: Method validation is done according to the ICH Guidelines (Q2) for the estimation of ceftriaxone in rat serum and its CSF (cerebrospinal fluid) by the RP-UFLC method. The blood was collected from the rat tail vein and CSF was collected carefully from cisterna magna of the rats by a 23G syringe. The mobile phase was used in a ratio of 70:30%v/v of phosphate buffer with ion-pairing reagent and acetonitrile with a pH of 8.0 Results: Limit of detection and limit of quantification of ceftriaxone in rat serum was 1.08 μg/ml and 3.84 μg/ml, respectively. Similarly, the limit of detection and limit of quantification of ceftriaxone in CSF of rats was 0.94 μg/ml and 2.84 μg/ml, respectively. In both cases, the R2 value was more than 0.99 and showed 99% accuracy. Conclusion: The experimental results suggest that the new RP-UFLC method developed and validated can be effectively used to assess ceftriaxone in preclinical studies in rats.
Keywords: recovery data